Conciliation procedures in their relationship with scientific categories of civil procedure - Oksana N. Zdrok (Правоприменение)
The subject of the paper is conciliation procedures as a phenomenon of the modern civil process.The purpose of the article is to confirm or disprove hypothesis that the relations arising between the participants of judicial conciliation procedures are procedural legal relations. It leads to the expansion of the subject of legal regulation of civil procedural law.The research was carried out with use of main scientific methods (analysis, induction and deduction), special (statistical) method as well as the method of interpretation of the legal acts.The main results and scope of their application. The paper shows the theoretical development of the matter of the relationship of the concept of “conciliation procedures” and such categories as “civil procedure”, “civil procedural form”, “civil procedural legal relations”. The solution of this scientific problem has fundamental theoretical and methodological significance for substantiating the place of conciliation procedures in the civil process system. Given the trend of strengthening of the private law elements of the civil process, the author advocates the need to revise the traditional approaches of the definition of the concepts of “civil procedure” and “civil procedural legal relations”. The author supports the point of view of the possibility of the existence of not only vertical (between court and trial participants), but also horizontal (between participants in the process) procedural legal relations. From this point of view, the relations arising between the participants of judicial conciliation procedures can be attributed to procedural legal relations. The author also joins the position of those scholars who advocate a broad understanding of civil proceedings as a combination of various judicial procedures, not all of which should correspond to the signs of civil procedure form.Conclusions. Entrusting the court with the function of reconciliation in civil and economic cases substantially changes the established concept of civil procedure as an exclusively jurisdictional process. So the subject civil procedure is not only the competitive activities of private dispute parties on proving a certain evidential composition required by the court to enforce the law and a resolute the dispute. On this basis, the author puts forward a thesis on the expansion of the object of legal regulation of civil procedural law.